1999
DOI: 10.1016/s0014-5793(99)01548-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the P450 catalytic cycle: yeast cytochrome b5/NADH cytochrome b5 reductase complex efficiently drives the entire sterol 14‐demethylation (CYP51) reaction

Abstract: The widely accepted catalytic cycle of cytochromes P450 (CYP) involves the electron transfer from NADPH cytochrome P450 reductase (CPR), with a potential for second electron donation from the microsomal cytochrome b 5 /NADH cytochrome b 5 reductase system. The latter system only supported CYP reactions inefficiently. Using purified proteins including Candida albicans CYP51 and yeast NADPH cytochrome P450 reductase, cytochrome b 5 and NADH cytochrome b 5 reductase, we show here that fungal CYP51 mediated sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 41 publications
3
69
1
2
Order By: Relevance
“…These results confirm the critical role of CYPOR in embryonic development and are consistent with the report that RNA-mediated interference of CYPOR expression in the nematode Caenorhabditis elegans produces embryonic lethality and undefined structural abnormalities (26). Although yeast are able to survive in the absence of CYPOR, with cytochrome b 5 serving as an alternate electron donor to the cytochromes P450 (9,10), it is clear that the functions of CYPOR are essential in higher organisms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results confirm the critical role of CYPOR in embryonic development and are consistent with the report that RNA-mediated interference of CYPOR expression in the nematode Caenorhabditis elegans produces embryonic lethality and undefined structural abnormalities (26). Although yeast are able to survive in the absence of CYPOR, with cytochrome b 5 serving as an alternate electron donor to the cytochromes P450 (9,10), it is clear that the functions of CYPOR are essential in higher organisms.…”
Section: Discussionsupporting
confidence: 89%
“…Electron transfer to the cytochromes P450 as well as membrane anchoring requires the hydrophobic, N-terminal membrane-binding domain of this microsomal flavoprotein (6,7). No other physiological electron donor to the cytochromes P450 has been identified in vertebrates, although plants contain multiple CYPOR genes (8) and electron transfer from the cytochrome b 5 /cytochrome b 5 system to P450 has been reported in yeast lacking CYPOR (9,10). Development of the mammalian embryo requires temporally and spatially regulated biosynthesis and degradation of signaling factors, many of which, such as retinoic acid, sterols, prostaglandins, and steroids, are dependent upon cytochrome P450 or other CYPOR-dependent pathways.…”
Section: Nadph-cytochrome P450 Oxidoreductase (Cypor)mentioning
confidence: 99%
“…Sequential oxidations at a single carbon atom that are mediated by cytochrome P450s have been described as, for example, in the loss of C-14 in steroid biosynthesis (30) and the three-step oxidation of ent-kaurene to ent-kaurenoic acid in G. fujikuroi (8). However, the reactions catalyzed by P450-1 involve oxidations The mass spectrometric data are provided as Table 2, which is published as supplemental data on the PNAS web site, www.pnas.org.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes: ERG1, squalene epoxidase; ERG7, lanosterol synthase; ERG11 (CYP51), lanosterol C-14 demethylase; ERG24, sterol C-14 reductase; ERG25, sterol C-4 methyloxydase; ERG26, sterol C-3 dehydrogenase (C4-decarboxylase); ERG27, sterol C-3 ketoreductase; ERG6, sterol C-24 methyltransferase; ERG2, sterol C-8 isomerase; ERG3, sterol C-5 desaturase; ERG5, sterol C-22 desaturase; ERG4, sterol C-24 reductase; ACAT (ARE1,2), acyl-CoA sterol acyl transferases. 113 However, by using various physiological modulations of the cellular NADH level during transitions from anaerobic (classical laboratory and enological) to aerobic conditions, it has been shown that the oxygen uptake due to sterol synthesis (i.e. terbinafine-and fenpropimorph-sensitive O 2 consumption) does not correlate with the cellular NADH redox state 168 (Rosenfeld et al, unpublished data).…”
Section: Oxygen-dependent Sterol Synthesismentioning
confidence: 99%